Modelling thermodynamic properties of banana waste by analytical derivation of desorption isotherms - Villa-Vélez, Harvey A. [UNESP]; Váquiro, Henry A.; Bon, José; Telis-Romero, Javier [UNESP] (De Gruyter, 2012)
Banana is an agricultural product of great economic importance for various developing countries. The relationship between moisture content and water activity provides useful information for the processing and storage of banana waste. The water activity and moisture content of three banana (Mussa spp. Haploid AAB cv. Nanica) waste items were analyzed to determine the desorption isotherms at six different temperatures (20, 30, 40, 50, 60 and 70°C). The desorption isotherms of the peel, pedicel and pulp of overripe bananas were determined in wide ranges of moisture content (0.001-6.360 kg kg-1 d.b.) and water activity (0.02-0.907). The theoretical GAB model was used for modelling the desorption isotherms. An analytical solution of the Clausius-Clapeyron equation was proposed to compute the isosteric heat of sorption, the differential entropy and Gibbs' free energy by way of the GAB model when the effect of temperature on the hygroscopic equilibrium was considered. © 2012 de Gruyter. All rights reserved.
Keywords: Banana waste; GAB model; Isosteric heat of sorption; Sorption isotherms; Thermodynamic properties; Water activity; Banana wastes; Adsorption isotherms; Agricultural products; Developing countries; Driers (materials); Moisture determination; Fruits; Mussa